PET Fibers Modified with Cloisite Nanoclay - Fabia, Janusz (Polymers (Basel), 2020)
The alternative method of reducing the flammability of polyethylene terephthalate (PET) fibers, analogous to dyeing of PET fibers with dispersed dyes in a high-temperature bath, was proposed. A commercial organophilic montmorillonite Cloisite(®)15A (C15A) was applied as a flame retardant. The aim of the presented work was to evaluate the effectiveness of the introduced modifier and the improvement of the flame-retardant properties of PET fibers by limiting oxygen index (LOI) and thermogravimetric analysis (TGA) measurements. Evolved gas analysis (EGA) by spectrometric method (FTIR) during coupled thermogravimetric analysis (TGA) was applied in order to confirm no increase in the toxicity of volatile degradation products released from burning modified fibers. The nanocomposite nature of modified fibers was confirmed based on the structural parameters of the fibers determined using wide-angle X-ray scattering (WAXS) and small angle X-ray scattering (SAXS) X-ray diffraction methods.